P-OGC38 The Impact of the COVID-19 Pandemic on Barrett's Oesophagus and Oesophago-gastric Cancer. (16th December 2021) - Turkington, Richard C; Lavery, Anita; Donnelly, David; Gavin, Anna T; McManus, Damian T; Cairnduff, Victoria; McShane, Charlene M; Johnston, Brian T; Anderson, Lesley A; Coleman, Helen G
Abstract: Background: The COVID-19 pandemic has placed an inexorable strain on endoscopy services worldwide, affecting the diagnosis of oesophago-gastric (OG) cancer and Barrett's oesophagus (BO). As coronavirus infection rates rose many professional bodies advised that all endoscopy, except emergency and essential procedures be stopped immediately. We sought to quantify the decline in OG cancer and BO diagnoses following implementation of British Society of Gastroenterology (BSG) guidance related to COVID-19 and the psychosocial effects on BO patients. Methods: We examined OG cancer and BO diagnoses in Northern Ireland from March-September 2020 and compared them with the three-year average number of patients during the same time period (corresponding to weeks 10-37) between 2017-2019 by utilising Northern Ireland Cancer Registry (NICR) data. The psychosocial impact of COVID-19 was assessed using an online survey, which included validated WHOQOL-BREF and EQ-5D-5L quality of life measures, and was completed by 24 BO patients from April-May 2020. Results: Between March and September 2020 in Northern Ireland, the proportion of OG cancer and BO diagnoses declined by 26.6% and 59.3%, respectively, compared to expected levels. In April, BO diagnoses fell by 95.5% but by September, whilst OG cancer rates had returned to baseline, BO cases remained supressed by approximately 20%. We estimate that these declines in diagnosis represent 53 'missed' OG cancer and 236 'missed' BO diagnoses. In the online survey sample, BO patients reported consistently lower quality of life scores than population norms, and highlighted a number of concerns with regard to their health and care. Conclusions: The COVID-19 pandemic has resulted in an abrupt decline in OG cancer and BO diagnoses and has profoundly impacted the wellbeing of BO patients. Our study represents the first report of the impact of COVID-19 on the diagnosis of BO. Strategies to mitigate the ongoing effects of the pandemic are urgently required to preserve the ability to rapidly detect and diagnose cancer and pre-malignant conditions.